(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2017)
We are living in an era where the meaning of digital continues to change over time as new technologies, user devices are invented. A detail study in this context shows that the Man is influenced by both internal and external forces. The evolution of technology in daily life and social organization has led to the fact that the modernization of information and communication processes has become the driving force of social evolution.This Paper explores some knowledge of “SELF” in digital Age from the perspective of Shrimad-Bhagvad-Gita philosophy which is 5,000 years old. A description has been given on self-knowledge that begins with self-observation, self-examination and self-evaluation. It also approach us to practice austerity of body, mind and speech to unfold the layers of self-glamour and illusion so that the truth is revealed for what they are, the deeper knowledge about the self. Self-knowledge brings in better understanding of the forces which influence man so that he can better understand his inner will or intention. In this paper, some perspectives of self-knowledge from the Bhagavad-Gita has been presented which will enlightens us with several lessons on the knowledge of self and the era in which we are living now.